Realitas Gugat Cerai TKW (Asia Timur) di Kabupaten Ponorogo: Sebuah Tinjauan Hukum Islam - Muawwanah, Rohana (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
This study aims to explore the phenomenon of divorce among migrant workers (TKW) who work in East Asia who made a lawsuit in the Ponorogo Regency Religious Court (PA) in year 2017. This study used a qualitative approach to the design of case studies. The results of the study show that the main factors causing divorce for TKW can be grouped into 3 factors, namely; economy, environment, and responsibility. These three factors give rise to the reasons used in filing a claim, namely; not providing a living, husband being sentenced to prison, morality (infidelity), husband disappearing, and domestic disharmony. Supporting factors for the divorce claim are strong supported by the level of education, family support and information technology. From the factors and reasons for the divorce, in the view of Islamic law can be grouped into three groups; mubah, makruh and haram.